Ethics and aesthetics in Toni Morrison's fiction - Palladino, Mariangela (Costerus, 2018)
Ethics and Aesthetics in Toni Morrison's Fiction investigates Morrison's aesthetics in terms of narrative's ethical import. Morrison's writing is concerned with ethically debatable issues and it offers a problematic representation of human experiences in African American history. Whilst previous critical studies consider ethics in relation to events in the story, Palladino explores its intersection with aesthetics. Narrativizing the moral law, Morrison's imperative is to relate the past, and to find ways to tell what is often unspeakable. The quest for ways to narrate horrific facts is a quest for an aesthetics which includes an appeal to the reader and thus necessarily engages with the ethical. This study foregrounds the equivocal as a key feature of narrative ethics.